Poronia radicata Hembrom, A. Parihar & K. Das, A new record from Maharashtra State, India - Rajendra, Patil Anjali; Prakash, Patil Ketaki (International Journal of Biological Research, 2016)
Family Xylariaceae is represented from India by 187 species belonging to 12 genera till date. Genus Poronia Willdenow ex SF Gray was reported for the first time from Kolkata in 2013. During the present mycological exploration, the species Poronia radicata Hembrom, A. Parihar & K. Das, a coprophillous member of family Xylariaceae was collected and studied. This is the second report from the Indian sub-continent and first from state of Maharashtra, India. Thus, it makes a new report to the fungi of Maharashtra.